Lettres apostoliques de s.s. Léon XIII encycliques, brefs etc - Catholic Church Pope (1878-1903 : Leo XIII); Leo XIII, Pope, 1810-1903.; University of Toronto (Paris Maison de la Bonne Press, 1890)
v. 2. 10 nov. 1884-20 nov. 1890 -- v. 3. 20 nov. 1890-25 oct. 1893 -- v. 4. 18 nov. 1893-4 mai 1896 -- v. 5. 29 juin 1896-22 jan. 1899 -- v. 6. 11 avr. 1899-28 mai 1902.
French and Latin on opposite pages. - Includes index (v.5)
Keywords: Leo -- XIII -- Pope -- 1810-1903 -- Papal documents; Catholic Church -- Pope (1878-1903 : Leo XIII); Papal Documents; Catholic Church